Super-enhancer associated core regulatory circuits mediate susceptibility to retinoic acid in neuroblastoma cells - Gomez, Roshna Lawrence; Woods, Laura M.; Ramachandran, Revathy; Abou Tayoun, Ahmad N.; Philpott, Anna; Ali, Fahad R. (Frontiers in Cell and Developmental Biology, 2022)
Neuroblastoma is a pediatric tumour that accounts for more than 15% of cancer-related deaths in children. High-risk tumours are often difficult to treat, and patients' survival chances are less than 50%. Retinoic acid treatment is part of the maintenance therapy given to neuroblastoma patients; however, not all tumours differentiate in response to retinoic acid. Within neuroblastoma tumors, two phenotypically distinct cell types have been identified based on their super-enhancer landscape and transcriptional core regulatory circuitries: adrenergic (ADRN) and mesenchymal (MES). We hypothesized that the distinct super-enhancers in these different tumour cells mediate differential response to retinoic acid. To this end, three different neuroblastoma cell lines, ADRN (MYCN amplified and non-amplified) and MES cells, were treated with retinoic acid, and changes in the super-enhancer landscape upon treatment and after subsequent removal of retinoic acid was studied. Using ChIP-seq for the active histone mark H3K27ac, paired with RNA-seq, we compared the super-enhancer landscape in cells that undergo neuronal differentiation in response to retinoic acid versus those that fail to differentiate and identified unique super-enhancers associated with neuronal differentiation. Among the ADRN cells that respond to treatment, MYCN-amplified cells remain differentiated upon removal of retinoic acid, whereas MYCN non-amplified cells revert to an undifferentiated state, allowing for the identification of super-enhancers responsible for maintaining differentiation. This study identifies key super-enhancers that are crucial for retinoic acid-mediated differentiation.